2019
DOI: 10.1002/wat2.1386
|View full text |Cite
|
Sign up to set email alerts
|

Are catchments leaky?

Abstract: Catchments, generally understood as the drainage areas of low‐order streams, are often regarded as closed hydrologic entities; that is, precipitation (P) minus evapotranspiration (ET) over a catchment equates stream outflow (Q r). Here, we review evidence that catchments can be leaky due to groundwater outflow or inflow across topographic divides, based on catchment mass balance across a continent and several site‐based studies across the globe. It appears that a catchment is more likely to be leaky with the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
130
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(140 citation statements)
references
References 50 publications
10
130
0
Order By: Relevance
“…Additionally, mountain hydrological studies sometimes assume that all groundwater recharges are returned to a river within the surface watershed. This assumption must be carefully examined as small headwater catchments are more likely than other catchments to be "leaky" in that groundwater export is a non-negligible component of the water balance (Fan, 2019).…”
Section: Box 1 Integrating Our Understanding Of Surface and Subsurfacmentioning
confidence: 99%
“…Additionally, mountain hydrological studies sometimes assume that all groundwater recharges are returned to a river within the surface watershed. This assumption must be carefully examined as small headwater catchments are more likely than other catchments to be "leaky" in that groundwater export is a non-negligible component of the water balance (Fan, 2019).…”
Section: Box 1 Integrating Our Understanding Of Surface and Subsurfacmentioning
confidence: 99%
“…Subsurface catchment properties can act as a particularly strong filter on climate variability. Large groundwater systems tend to filter out short‐term variation and instead show more pronounced multi‐annual to decadal‐scale variation (e.g., Cuthbert et al, ; Hanson, Dettinger, & Newhouse, ; Sidibe et al, ), which may also be transferred to or received from areas beyond the catchment boundary (Bouaziz et al, ; Fan, ). In contrast, short‐term (up to interannual) variations tend to be dominant in steep catchments with shallow groundwater systems (Sidibe et al, ) or in catchments with strong subsurface heterogeneity (Hartmann, ).…”
Section: Framing Hydrological Processes In a Larger‐scale Contextmentioning
confidence: 99%
“…In catchment hydrology, topographically delineated catchments represent the common units for studies at catchment scale, e.g., hydrological simulations of the catchment responses (Clark et al, 2017;Kirchner, 2009), drought and flood analyses (Haslinger et al, 2014;Merz & Blöschl, 2005;Tallaksen et al, 2009), sediment production and transport from hillslopes to rivers (Liu et al, 2018;Sherriff et al, 2016;Zuo et al, 2016), and the behavior and fate of nutrients and pollutants (Liu et al, 2019;Van Meter & Basu, 2017;Pullan et al, 2016). However, previous work showed that the water balance of topographic catchments may often not be closed (Fan, 2019;Le Mesnil et al, 2020). This is particularly true for karstic regions where recharge areas are often found to not be equal to the topographic catchment.…”
Section: Introductionmentioning
confidence: 99%